2008
DOI: 10.1063/1.2969063
|View full text |Cite
|
Sign up to set email alerts
|

ArF laser-based quantum well intermixing in InGaAs/InGaAsP heterostructures

Abstract: Radiation from a 193 nm ArF laser was investigated to modify surface properties of InGaAs/InGaAsP quantum well (QW) heterostructures and introduce defects required to enhance intermixing during the annealing process. A top 200 nm thick sacrificial layer of InP served as a reservoir for laser generated defects. The irradiation with up to 90 pulses at 65–150 mJ/cm2 allowed to generate an array of 1.2×1 mm2 sites of QW intermixed material, with bandgap energy blueshifted up to 107 nm. We discuss the mechanism and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
2
2

Relationship

5
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…We are proposing here an innovative use of the MSSLD design: thanks to the UV Laser Quantum Well Intermixing (UV-QWI) process developed at Université de Sherbrooke [5], a SLD consisting of several different bandgap energy sections was developed, each section being driven by a different electrode, allowing an important versatility on output spectral width and power.…”
Section: Superluminescentmentioning
confidence: 99%
“…We are proposing here an innovative use of the MSSLD design: thanks to the UV Laser Quantum Well Intermixing (UV-QWI) process developed at Université de Sherbrooke [5], a SLD consisting of several different bandgap energy sections was developed, each section being driven by a different electrode, allowing an important versatility on output spectral width and power.…”
Section: Superluminescentmentioning
confidence: 99%
“…indium oxides and gallium oxides, have significantly increased in the excimer laser irradiated sites. 6,8 From secondary ion mass spectroscopy (SIMS) measurements, it has been reported that on InP based QW structures, In and Ga atoms are easier to outdiffuse to the SiO 2-x layer and create V interstitials that enhance interdiffusion between barrier and well materials during RTA. 9 XPS depth profiling results also demonstrated that the total concentration of In and Ga atoms outdiffusing to the SiO 2 layer could be at around 0.5 at.…”
Section: Introductionmentioning
confidence: 99%
“…3 We have been investigating the ability of UV lasers to modify surface properties of III-V quantum well (QW) microstructures and generate defects capable of promoting the process of QW intermixing (QWI). [4][5][6] Excimer lasers are known to modify the surface chemical composition of InP-and GaAs-based QW microstructures irradiated in air and lead to a significantly enhanced interdiffusion between the well and barrier materials during high temperature rapid thermal annealing (RTA). 6-8 X-ray photoelectron spectroscopy (XPS) measurements have demonstrated that the amount of oxides, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Among these processes, ultraviolet laser-induced quantum well intermixing (UV-Laser-QWI) is particularly appealing due to its ability to produce selective area bandgap tuned wafers without employing contact masking and associated processing steps. In addition to pulsed IR laser QWI [19,20], both visible [21] and pulsed UV [22,23] lasers have been investigated for the intermixing and selective are bandgap engineering.…”
Section: Introductionmentioning
confidence: 99%